2020
DOI: 10.2147/ott.s240378
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of RAGE Inhibits Cell Proliferation and Induces Apoptosis via Regulation of PI3K/AKT Pathway in Cervical Squamous Cell Carcinoma</p>

Abstract: Aim: The receptor for advanced glycation endproducts (RAGE) expression has been reported to be implicated with cancer development. In this study, the role of RAGE in the regulation of cervical squamous cancer cell proliferation, apoptosis and the mechanism of RAGE involved in the biological behaviors were explored. Methods: The RAGE expression was overexpressed or downregulated by lentivirus transfection. The effect of RAGE expression on cell proliferation was explored by CCK-8, MTT, and BrdU assay, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…As shown in many studies mentioned in this review investigating the role of RAGE by its blockage through siRNA and antibodies and antagonists treatment, RAGE activation stopped, as well as underlying mechanisms leading to tumorigenicity. Also, it has been indicated that antibodies against RAGE ligands can decrease the risk of CRC (178)(179)(180)(181)(182). This, as mentioned before, the effect of prolonged RAGE blockade in human subjects is important because RAGE plays vital roles in normal physiology.…”
Section: Therapeutic Strategies Against Rage In Crcmentioning
confidence: 81%
“…As shown in many studies mentioned in this review investigating the role of RAGE by its blockage through siRNA and antibodies and antagonists treatment, RAGE activation stopped, as well as underlying mechanisms leading to tumorigenicity. Also, it has been indicated that antibodies against RAGE ligands can decrease the risk of CRC (178)(179)(180)(181)(182). This, as mentioned before, the effect of prolonged RAGE blockade in human subjects is important because RAGE plays vital roles in normal physiology.…”
Section: Therapeutic Strategies Against Rage In Crcmentioning
confidence: 81%
“…It transports only Aβ in circulation into the brain, but not out of the brain [ 14 ]. More studies have found that RAGE is involved in cell proliferation and apoptosis [ 15 , 16 ], including neurons [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that CC cells express high levels of PI3K, Akt, and phosphorylated Akt [44][45][46]. Moreover, treatment with PI3K/ Akt pathway inhibitors prevented cell proliferation [47], induced apoptosis [48], and restored metastasis [49] in CC. These results illustrated that the PI3K/Akt pathway may be a novel biomarker for predicting the prognosis of CC and a potential target for developing new treatment for such tumors [50].…”
Section: Discussionmentioning
confidence: 99%